Nilai-Nilai Kearifan Lokal dan Moderasi Beragama dalam Tradisi Bersih Desa Tanjung Sari di Dlimas Klaten - Jaenuri, Jaenuri (INCARE, International Journal of Educational Resources, 2024)
This study aims to explore and analyze the values of local wisdom in the Tanjung Sari village cleaning tradition in Dlimas Village, Klaten, and its role in promoting religious moderation. This tradition serves not only as a ritual for cleanliness and environmental health but also as a medium for teaching social values, tolerance, and interfaith harmony. Using a qualitative approach, this research investigates the symbols within the ritual and examines its role in strengthening social character and religious moderation in a diverse society. The findings indicate that the Tanjung Sari village cleaning tradition has the potential to function as a socio-political control mechanism that can reduce social tensions and foster harmony in the community. This research is expected to contribute to the preservation of local wisdom and the development of character education in Indonesia.